Potassium isotope fractionation during continental weathering and implications for global K isotopic balance. (1st June 2020) - Teng, Fang-Zhen; Hu, Yan; Ma, Jin-Long; Wei, Gang-Jian; Rudnick, Roberta L.
Abstract: Potassium isotopic compositions of profiles through saprolites developed on a diabase in South Carolina, U.S.A., and on a granite in Guangdong, China, allow characterization of the behavior of K isotopes during continental weathering. Saprolites from the diabase profile are heavily weathered with chemical index of alteration (CIA) values up to 95; however, their K isotopic variation is limited, with δ 41 K ranging from −0.475 ± 0.028‰ in the unweathered diabase to −0.407 ± 0.021‰ for the saprolites. The lack of significant K isotope fractionation mainly reflects the conservative behavior of K in the diabase weathering profile, with >50% of the original K remaining in the saprolites. By contrast, K isotopes are fractionated during granite weathering and correlate with sample depth, CIA, and kaolinite abundance, with δ 41 K decreasing from −0.493 ± 0.030‰ in the unweathered granites at the bottom to −0.628 ± 0.021‰ in the most weathered saprolite close to the surface. These observations suggest the preference of light K isotopes in saprolites relative to fluids, which is further supported by the overall isotopically heavy nearby stream water samples (δ 41 K = −0.709 ± 0.017 to −0.339 ± 0.018‰). These results demonstrate that continental weathering plays an important role in the global K isotopic budget through the formation of isotopically heterogeneous rivers and weathered regolith. Recycling of K-rich crustal materials with distinct K isotopic signatures may produce distinct mantle K isotopic end members.